2021
DOI: 10.1111/hex.13248
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use, cigarette smoking, vaping and number of sexual partners: A cross‐sectional study of sexually active, ethnically diverse, inner city adolescents

Abstract: Context There are few UK data on the prevalence and clustering of risky behaviours in ethnically diverse adolescents. Objectives To investigate the prevalence of reported alcohol use, smoking and vaping, and explore whether these behaviours are associated with increased numbers of sexual partners. Design Questionnaire survey of ‘Test n Treat’ chlamydia screening trial participants. Setting and participants Sexually active students attending six London technical colleges completed confidential questionnaires an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…This shows that substance abuse or addiction is linked to RSB. A number of studies have also identified that alcohol and smoking are associated with increased number of sexual partners, early initiation of unsafe sex, and other risky sexual behaviours [4,42,43]. Besides, information about HIV/AIDS is important to prevent RSB among women and men in the age of 15-49 years, as evidenced by the finding of this study that the odds of having RSB among study subjects who have never heard of HIV/AIDS was 1.9 times higher as compared to their counterparts.…”
Section: Plos Onementioning
confidence: 99%
“…This shows that substance abuse or addiction is linked to RSB. A number of studies have also identified that alcohol and smoking are associated with increased number of sexual partners, early initiation of unsafe sex, and other risky sexual behaviours [4,42,43]. Besides, information about HIV/AIDS is important to prevent RSB among women and men in the age of 15-49 years, as evidenced by the finding of this study that the odds of having RSB among study subjects who have never heard of HIV/AIDS was 1.9 times higher as compared to their counterparts.…”
Section: Plos Onementioning
confidence: 99%
“…2 Alcohol exposure can have a widespread impact on the physical and mental health of young adults. Studies have shown that alcohol exposure in young adults increased the risk of gambling, 3 smoking, 4 drug use, 5 and violence. 6 At the same time, it can also increase the risk of cardiovascular diseases, 7 digestive diseases, 8 cancers, 9 and other diseases 10 in later life.…”
Section: Introductionmentioning
confidence: 99%